Quantum-statistical T-matrix approach to line broadening of hydrogen in dense plasmas - Lorenzen, S.; Wierling, A.; Reinholz, H.; Röpke, G.; Zammit, Mark; Fursa, Dmitry; Bray, Igor (2010)
The electronic self-energy Se is an important input in a quantum-statistical theory for spectral line profile calculations. It describes the influence of plasma electrons on bound state properties. In dense plasmas, the effect of strong, i.e. close, electron-emitter collisions can be considered by three-particle T-matrix diagrams. These digrams are approximated with the help of an effective two-particle T-matrix, which is obtained from convergent close-coupling calculations with Debye screening. A comparison with other theories is carried out for the 2p level of hydrogen at kBT = 1 eV and ne = 2· 1023 m-3, and results are given for ne = 1 ·1025 m-3. © 2010 American Institute of Physics.